Calibration of laboratory equipment based on official standards. - Pacheco, M.; García, P.; Montes, H. (Revista Mexicana de Ingenieria Biomedica, 1989)
In the present work, the variables to be controlled of the UV-visible spectrophotometers, pH meters, analytical scales and dissolves are exposed and discussed; covering in each case the verification and calibration tests that were found most useful.